Atlas of clinical dermatology - DuVivier, Anthony; McKee, Phillip H (Churchill Livingstone, 2002)
The third edition of the Atlas of Clinical Dermatology is a thorough, comprehensive update of the world\'s leading visual reference in dermatology. It is lavishly illustrated with over 2000 exceptional photographs, in vivid colour, from Dr du Vivier\'s unrivalled clinical collection. The accompanying text clearly, succinctly and comprehensively covers the aetiology, clinical features, diagnosis and treatment of each disease. Although the focus is on common conditions, rare diseases and manifestations are also featured. This book covers all the clinical aspects of skin diseases with an emphasis on achieving accurate diagnosis. The Atlas of Clinical Dermatology is an essential purchase for all practising and trainee dermatologists.
Keywords: dermatologie; dermatovenerologie; Dermatology